Parents' Seven Strategies to Build Children's Social Character since Early - Fransisca, Ria; Az-zahra, Dwi Wahyuni; Setianingrum, Indah (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2023)
The family provides the social and environmental relationships that are important for a child's first learning needs. Parents as the head of the family are called to be educators for children. The family is the first socialization place for children and is tasked with instilling moral and social values. Through interactions within the family, children not only get to know themselves and their parents but also get to know the life of the community and the surrounding environment. Early childhood follows parents from various habits and behaviors, when children interact with other people, it is at this time that meaningful events will occur to shape their personality. By inviting children to participate in social activities, such as staying in touch, mutual cooperation, sharing, greeting, being friendly, working together and playing together, children can have a good relationship with their surroundings. The purpose of this review is to present empirical evidence about strengthening social character in early childhood, stimulation carried out by parents in the family, and parenting in strengthening children's social character.